EXPERT SYSTEM FOR TROUBLESHOOTING LAPTOP MOTHERBOARD DAMAGE USING FORWARD CHAINING METHOD AT BUDI DARMA UNIVERSITY COMPUTER LAB - Hery Sunandar; Berto Nadeak; Pristiwanto; Saidi Ramadan Siregar (Sean Institute, 2020)
The development of laptop hardware technology in the 21st century is increasingly rapid to support information technology that is increasingly easily accessed. Laptops have an important role in helping human activities, especially in teaching and learning activities. Not infrequently a laptop or better known as a laptop as most students and lecturers and even students who sit in secondary education have started to use it. In national tertiary education, the entire campus requires both public and private universities to have laptop laboratories. Along with these developments in the case of laptop usage is getting bigger.